Numerical solution of hybrid method for third grade flow due to variable accelerated plate in a rotating frame - Mahadi, Shafaruniza; Abdul Aziz, Zainal; Su Hoe, Yeak; Salah, Faisal; Suraya Md Nasrudin, Farah (International Journal of Engineering and Technology, 2018)
The aim of this article is to obtain numerical solution for incompressible unsteady flow for third grade fluid induced by variable accelerated plate. Numerical solution is obtained by using Hybrid method which combine between finite difference method (FDM) and asymptotic interpolation method. The influence of difference values of material constant parameters on the velocity flow fluid are discussed and shown graphically.Â